Insight into improved specificity and thermostability of Geobacillus zalihae T1 lipase by introducing novel molecular interactions via phenylalanin to cysteine substitution - Albayati, Samah Hashim; Shabeeb, Muna Hilal; Akinola, Oluwasola Michael; Nezhad, Nima Ghahremani; Chor, Adam Leow Thean; Mohamad Ali, Mohd Shukuri; Mohd Shariff, Fairolniza; Muhd Noor, Noor Dina; Abd Rahman, Raja Noor Zaliha Raja (Springer Science and Business Media Deutschland GmbH, 2025)
Lipase specificity is a crucial requirement for industrial employment; however, tuning the lipase specificity in some cases can impair the structure and affect its stability. To enhance the T1 lipase specificity, we targeted the conserved bulky residue Phe180 in the lid domain to eliminate the impact of steric hindrance, as it constrains substrate accession to the enzyme active site and affects specificity. This residue was pre-substituted with a small side chain residue by utilizing DynaMut2 software to ensure that this substitution did not affect lipase stability. Phe180Cys was chosen because it exhibited a stabilizing effect by showing (ΔΔGStability) of 0.74 kcal/mol, which was subsequently substituted by the rational design approach. This variant has successfully exhibited specificity modification toward long fatty acid chains as a result of increasing the distance between the lid domain and catalytic site by 1.2 Å and the volume of active site by 190.2 Å3. In addition, this F180C variant exhibited an increase in the optimum temperature and thermal denaturation point to 75 °C and 78 °C, respectively, with an improvement in the lipase stability in the organic solvents. The analysis of the atomic interactions revealed a change in the whole H-bonds, S/π interactions, and salt bridge network. The biophysical study revealed changes in the secondary structure content compared with wt-T1. The MD simulation results displayed lower RMSD, gyration radius, and SASA values for the mutated lipase structure. In conclusion, comparative analysis of the atomic interactions resulting from structural modification can significantly elucidate the specificity and thermostability of enzymes of industrial relevance.